2010
DOI: 10.1177/0961203310385267
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis of severe lupus nephritis based on the Modification of Diet in Renal Disease (MDRD) Study estimated glomerular filtration rate

Abstract: The level of renal function at biopsy is predictive of outcome in patients with severe lupus nephritis (SLN). While renal function has been based on serum creatinine (SCr) alone, measuring the estimated glomerular filtration rate (eGFR) utilizing the Modification of Diet in Renal Disease (MDRD) Study equation has been found to be more accurate. The MDRD eGFR (ml/min/1.73 m(2)) at biopsy was calculated in 86 patients with SLN and patients were categorized based on eGFR: ≥60 (33 pts), 59-30 (33 pts) and <30 (20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Hence, it seems natural that in the field of procedural pulmonary medicine, educators and leaders are advocating the cause of standard procedural curricula and competency assessments [2,3,4,5,6,7,8,9]. Until recently, the bronchoscopic skill of trainees has been subjectively assessed by training program directors, and based in part on the number of procedures performed as well as on watching trainees perform procedures in patients during the course of postgraduate education.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it seems natural that in the field of procedural pulmonary medicine, educators and leaders are advocating the cause of standard procedural curricula and competency assessments [2,3,4,5,6,7,8,9]. Until recently, the bronchoscopic skill of trainees has been subjectively assessed by training program directors, and based in part on the number of procedures performed as well as on watching trainees perform procedures in patients during the course of postgraduate education.…”
Section: Resultsmentioning
confidence: 99%
“…Among pulmonary and critical care physicians, who perform the majority of these procedures for both diagnosis and therapy, a large degree of variation has been demonstrated in the way bronchoscopy is learned by trainees in pulmonary fellowship programs [1,2,3]. Many bronchoscopy educators have therefore advocated the design of standardized curricula in order to teach the knowledge and technical skills necessary for the safe and effective performance of this minimally invasive procedure [2,3,4,5,6,7,8,9]. …”
Section: Background and Rationalementioning
confidence: 99%
“…We included patients with class II and V disease because the diagnoses were made at the beginning of the induction phase with CYC; all of these patients had severe proteinuria and/or decreased eGFR when starting maintenance therapy (data not shown). We estimated renal function in our LN patients by using the MDRD eGFR equation, as recommended by Patel et al [10]. Considering that the role of MF in long-term treatment of severe LN remains unsolved [5], we think our results are useful for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Analytical variables included hemoglobin (g/dl), white cell counts (cells/mm 3 ), serum creatinine (mg/dl), estimated glomerular filtration rate (eGFR, ml/min/1.73 m 2 ) calculated using the 4-variable Modification of Diet in Renal Disease (MDRD) equation [eGFR = 175 × serum creatinine - 1.154 × age - 0.203 × 1.210 (if black) × 0.742 (if female)] [10], proteinuria (g/24 h), titers of antinuclear and anti-dsDNA antibody, and levels of complement fractions (C3 and C4, mg/dl). Types and doses of MF (mofetil or sodium), corticosteroids used as maintenance therapy, and antihypertensive drugs were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…We have not chosen serum creatinine as a marker of renal function since 8% of the patients with normal serum values (<1.2 mg/dl) have decreased eGFR. Patel et al [12] demonstrated that renal function in LN should be measured using eGFR rather than serum creatinine alone. …”
Section: Discussionmentioning
confidence: 99%